(untitled) (Global Journal of Science Frontier Research, 2017)
Universe consisted of mysterious Dark energy (70%), Dark matter(25%) and that make up now 95% of matter in the universe which revel it self as gravity. Enormous filaments and blobs of dark matter in early universe condensed as universe condensed. Within the cosmic webs, all galaxies, stars, planets were next created. Galaxies are not dotted randomly throughout universe but are generally either concentrated in groups or in clusters, which are connected again by multitude of filaments and voids. These filamentary distributions of galaxies explained by vast quantities of dark matter enveloping galaxies and filamentary cold gas flowing within them, responsible for star formation within them and the dark matter ISM is the dominant mass in the universe. Galaxies over passing time, clumped itself in a filamentary networks.